Lung transplant and severe coronary artery disease: results from a single-centre experience. (15th June 2022) - Franz, Maximilian; Siemeni, Thierry; Aburahma, Khalil; Yablonski, Pavel; Poyanmehr, Reza; Avsar, Murat; Bobylev, Dmitry; Sommer, Wiebke; Boethig, Dietmar; Greer, Mark; Gottlieb, Jens; Tudorache, Igor; et al.
Abstract: OBJECTIVES: The management of severe coronary artery disease at the time of a lung transplant remains a challenge. We analysed the short- and long-term outcomes of lung transplant recipients with severe coronary artery disease. METHODS: Records of adult patients who received transplants at our institution between April 2010 and February 2021 were reviewed retrospectively. Severe coronary artery disease was defined as coronary stenosis ≥70% (main stem ≥50%) seen on the coronary angiographic scans performed before or at the time of listing. Patient characteristics, perioperative and long-term outcomes were compared between patients with and without severe coronary artery disease. RESULTS: Among 896 patients who received lung transplants who had undergone coronary angiography before the transplant, 77 (8.5%) had severe coronary artery disease; the remaining 819 (91.5%) did not. Patients with severe coronary artery disease were older (p < 0.0001), more often male (p < 0.0001) and received transplants more often for pulmonary fibrosis (p = 0.0007). The median (interquartile range) follow-up was 46 (20–76) months. At the Cox multivariable analysis, severe coronary artery disease was not associated with death. Patients with pretransplant percutaneous transluminal coronary angioplasty and patients with coronary artery bypass graft surgery concomitant to a transplant had survival equivalent to that of patients without severe coronary artery disease (p = 0.513; p = 0.556). CONCLUSIONS: Severe coronary artery disease was not associated with decreased survival after a lung transplant. Concomitant coronary artery bypass graft surgery and pretransplant percutaneous transluminal coronary angioplasty can be used for revascularization.